2000
DOI: 10.1046/j.1439-0450.2000.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility ofArcanobacterium pyogenesIsolated from Cattle and Pigs

Abstract: The minimum inhibitory concentrations (MICs) of 18 antimicrobial agents were determined for 49 Arcanobacterium pyogenes isolates (42 bovine isolates and 7 porcine isolates). Benzylpenicillin and ampicillin were the most active antibiotics, with MIC ranges of < or = 0.0125-0.05 microgram/ml for both bovine and porcine isolates. All isolates were susceptible to penicillins and cephems. MICs for 90% of the isolates of dihydrostreptomycin, gentamicin and oxytetracycline for bovine isolates were > 100 micrograms/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 16 publications
(28 reference statements)
4
30
0
4
Order By: Relevance
“…A French study indicated that 67% of 103, predominantly bovine, A. pyogenes isolates were resistant to tetracycline, doxycycline, and minocycline (13), while a study in Japan found that 85.7% of porcine and 57.1% of bovine isolates were resistant to oxytetracycline and doxycycline (40). These results were confirmed by a recent study of predominantly North American isolates of A. pyogenes, which indicated that 42% were resistant to tetracycline, chlortetracycline, and oxytetracycline, with more than 70% of porcine isolates being resistant (34).…”
mentioning
confidence: 99%
“…A French study indicated that 67% of 103, predominantly bovine, A. pyogenes isolates were resistant to tetracycline, doxycycline, and minocycline (13), while a study in Japan found that 85.7% of porcine and 57.1% of bovine isolates were resistant to oxytetracycline and doxycycline (40). These results were confirmed by a recent study of predominantly North American isolates of A. pyogenes, which indicated that 42% were resistant to tetracycline, chlortetracycline, and oxytetracycline, with more than 70% of porcine isolates being resistant (34).…”
mentioning
confidence: 99%
“…It has been shown that in infected pig farms, 2 to 44% of female swine and pigs in the other sectors of production are culled and directed for slaughter each year (Yoshimura et al 2000, Pejsak et al 2006. The exact pathogenesis of the development of inflammatory lesions in the osteoarticular system is not fully understood.…”
Section: Disorders Of the Osteoarticular Systemmentioning
confidence: 99%
“…In the United States, tylosin is widely used as a feed additive to control liver abscessation in feedlot cattle (11). Resistance of the liver abscess pathogen, A. pyogenes, to macrolide antibiotics has been reported (4,25,28), but the mechanisms of resistance were not determined. This work is the first report of the identification and characterization of a determinant encoding tylosin resistance in A. pyogenes.…”
Section: Vol 47 2003 Erm(x) Encodes Tylosin Resistance In a Pyogenmentioning
confidence: 99%